CRISIS, UNCERTAINTY, RISK AND CONSUMER BEHAVIOR: A PSYCHO-ECONOMIC APPROACH - Mihaela DIACONU; Amalia DUTU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Quality of life has become in recent decades a concept approached as an important interface between many disciplines, such as economics, sociology, geography and medical science. Consumer behavior, an illustrative factor of quality of life is a complex process and is often not considered rational. Under current conditions, predicting consumer behavior is essential as all marketing decisions are based on their characteristics. The paper aims to highlight several specialized studies related to consumer behavior in crisis conditions in order to guide marketing decisions in special conditions, different from normal.